The Role of Trust in Relationship of Leadership Style and Organizational Effectiveness: Mediation Mechanism - ., S. Martono; Wiratno Putri, Vini; Ariani Wulansari, Nury; ., Moh. Khoiruddin (KnE Social Sciences, 2020)
This study is aimed at explaining the effect of leadership style to organizational effectiveness through trust as mediators. The number of samples of this study was 267 university employee respondents at Universitas Negeri Semarang. The sampling technique used was purposive sampling. The methods of collecting data used were observation, interview, and questionnaire. Hypothesis test used was path coefficient value which was done through t-test using Smart PLS 3.0. Leadership style directly gave positive effect to organizational effectiveness. Furthermore, mediation mechanism had been proven that trust gave important role in determining the relationship between leadership style and organizational effectiveness. This study was expected to contribute to management practice in the field of university in which university need pay attention to effective leadership to encourage employees’ trust. As a result, trust can encourage organizational effectiveness. This study also gave contribution to the development of leadership style literature and organizational effectiveness in the field of non-profit organization. This study attempted to answer the need of previous study by adding mediation variable. It was expected that mediation could explain the mechanism of the relationship between leadership style and organizational effectiveness completely. The scope of this study took university field that become novelty and generalization for the previous study.